Fracture load of tooth-implant-retained zirconia ceramic fixed dental prostheses: effect of span length and preparation design - Gabbert, Olaf; Karatzogiannis, Efstathios; Ohlmann, Brigitte; Schmitter, Marc; Karl, Jochen; Rammelsberg, Peter (Clinical oral implants research, 2012)
Objectives: Evaluation of the effect of different span length and preparation designs on the fracture load of tooth-implant-supported fixed dental prostheses (TIFDPs) manufactured from yttrium-stabilized zirconia frameworks. Material and methods: Forty-eight TIFDPs were manufactured using a CAD/CAM system and veneered with a press ceramic. Rigidly mounted implants (SLA, diameter 4.1 mm, length 10 mm) in the molar region with a titanium abutment were embedded in PMMA bases pairwise with premolars. All premolars were covered with heat-shrink tubing to simulate physiological tooth mobility. Six different test groups were prepared (a) differing in the preparation design of the premolar (inlay [i]; crown [c]), (b) the material of the premolar (metal [m]; natural human [h]) and (c) the length of the TIFDPs (3-unit [3]; 4-unit [4]). All TIFDPs underwent thermomechanical loading (TCML) (10,000 × 6.5°/60°; 6 × 105× 50 N). The load to fracture (N) was measured and fracture sites were evaluated macroscopically. Results: None of the restorations failed during TCML. The mean fracture loads (standard deviations) were 1,522 N (249) for the 3-unit, inlay-retained TIFDPs on a metal abutment tooth (3-im), 1,910 N (165) for the 3-cm group, 1,049 N (183) for group 4-im, 1,274 N (282) for group 4-cm, 1,229 N (174) for group 4-ih and 911 N (205) for group 4-ch. Initial damages within the veneering ceramic occurred before the final failure of the restoration. The corresponding loads were 24-52% lower than the fracture load values. Conclusions: All restorations tested could withstand the mastication forces expected. Fracture-load values for 3- and 4-unit inlay-crown and crown-crown-retained TIFDPs should spur further clinical investigation.
First published: 03 August 2011
Gesehen am 05.06.2018